CHEMOKINE (C-X-C MOTIF) RECEPTOR 4 REGULATES LUNG ENDOTHELIAL BARRIER PERMEABILITY DURING RESUSCITATION FROM HEMORRHAGIC SHOCK - Babu, Favin S. (Physiol Res, 2019)
Chemokine (C-X-C motif) receptor 4 (CXCR4) agonists have been shown to protect lung endothelial barrier function in vitro. In vivo effects of CXCR4 modulation on lung endothelial permeability are unknown. Here we tested the effects of the CXCR4 agonist ubiquitin and the antagonist AMD3100 on lung vascular permeability and cytokine concentrations in a rat hemorrhage model. Animals were hemorrhaged (mean arterial blood pressure 30 mmHg for 30 min), treated with vehicle, ubiquitin (0.7 and 3.5 µmol/kg) or AMD3100 (3.5 µmol/kg), and resuscitated with crystalloids. Evans blue extravasation was employed to quantify lung vascular permeability. Ubiquitin dose-dependently reduced Evans blue extravasation into the lung. AMD3100 increased Evans blue extravasation. With AMD3100, TNFα levels in lung homogenates were increased; while TNFα levels were lower with ubiquitin, these differences did not reach statistical significance. Our findings suggest that CXCR4 regulates lung vascular permeability and further point towards CXCR4 as a drug target to confer lung protection during resuscitation from traumatic-hemorrhagic shock.